A study on the noise characteristics of polymer ball bearings under various lubrication conditions - Dinç, S. K.; Temiz, V.; Kamburoğlu, E. (AIP, 2013)
Polymer bearings are generally praised by the manufacturers for running silently. However such statements never go beyond qualitative assumptions. Therefore, studying polymer ball bearing noise would have been meaningful solely on the perspective of silent running machinery. On the other hand, the service life of a polymer ball bearing is unpredictable and there's no preventive maintenance practice that provides data regarding the condition of a polymer ball bearing. In this study, we assume that an investigation of their noise characteristics could also reveal clues concerning their performances. The main objective of this study is to determine the noise characteristics of polymer ball bearings lubricated with different lubricant greases of varying viscosity grades through experimental means. Sound pressure level measurements of SKF brand polymer bearings with polypropylene rings, polypropylene cage and glass balls were made with a 12 inch microphone in 1/3-octave bands, at frequencies up to 12.5 kHz, un...